Process simulation and improvement of industrial acid gas removal unit (AGRU) - Nurfarah Aaina, Mohd Zulkifli (2009)
Acid gas removal process, which is also known as gas sweetening process, is a very important industrial operation that has been described in many works. The main processes installed are based on absorption, and the selection of the solvent is based on its capability to absorb or remove acid gases such as carbon dioxide (CO2) and hydrogen sulphide (H2S). Realizing such acid gases can cause operational problems such as corrosion and equipment plugging, the solvent used for absorption can be classified into chemical and physical types. The widely used absorption processes to sweeten natural gas are using chemical solvent such as alkanolamines or simply called “amine”. In this context, monoethanolamine (MEA) and methyldiethanolamine (MDEA) are among the most common amine used in the aqueous solution to remove both CO2 and H2S gases from natural gas stream. In this research, existing process flow diagram of industrial Acid Gas Removal Unit (AGRU) has been modified in terms of solvent used for absorption process. The mixture of MEA and MDEA in aqueous amine solution replaces the existing solvent known as Benfield solution. Simulation using Aspen Hysys is then performed to compare both existing and modified absorption processes according to four parameters, which are absorption column removal efficiency, power consumption, heating duty and cooling duty. The simulation results shows amine solution offers attractive solvent option to be used in improving existing AGRU system. For the same absorption column removal efficiency, amine solution can save 11.2% annual power consumption, which is equivalent to RM 967270 per year. Even though there is no change for heating duty, the cooling duty requirement however can be reduced by 17%, which saves about RM 27324 per year for the amine solution. These savings can be further analyzed when considering and comparing other aspects of operational experiences such as foaming, solvent degradation and corrosion problems.